MANUFACTURE OF MOTOR CYCLE CYLINDER LINER FROM METAL MATRIX COMPOSITES AL-SIC USING STIR CASTING METHOD - Ridwan Hamzah, Muhamad
Metal matrix composites (MMC) are metal materials whose performance has been improved by adding reinforcing particles that can be dispersed in the metal matrix in order to obtain new materials that have superior properties which are a combination of the unique properties of the constituent components. The increasing of MMC properties depends on the dispersion of the reinforcing particles in the metal matrix. For this reason, it is necessary to select the right parameters to achieve the dispertion SiC particle of the MMC. In this research, the manufacture of MMC for motorcycle cylinder liner applications uses aluminum 2024 as the matrix and silicon carbide (SiC) as the reinforcement. The process of making MMC uses a stirring rod following the concept of the stir casting method and the addition of Mg elements which functions to increase the wetting ability so that aluminum and SiC are easy to mix. To optimize the process, SiC is used with a composition of 10 wt% and Mg composition with a variation of 0 wt%, 0.5 wt%, 1 wt%, 1.5 wt%. Furthermore, to find out how much the composition of Mg to the dispersion in the aluminum matrix, characterization was carried out in the form of a metallographic test and a hardness test. From the test results, it was found that with the addition of 1 wt% Mg, the SiC particle dispersion was better than other variations in the composition of Mg. In general, the distribution of SiC particles in the aluminum matrix is not even and homogeneous so that the expected hardness has not been achieved. For the manufacture of cylinder liner products, it shows that the silicon carbide particles added are still wasted and have not been able to mix in the aluminum matrix.